The Impact of Principal Leadership and Teacher Work Encouragementon Teacher Performance - Nugroho, Fajar Wakhid; Ahyani, Nur; Eddy, Syaiful (Jurnal Pendidikan Tambusai, 2021)
The goal of this study is to decide whether the leadership and motivation of school principals has a very important impact on the performance of high school teachers in the PlakatTinggi District. The theoretical analysis presented is the concept of leadership, the understanding of motivation, the understanding of the principal and the success of the instructor, whereas the research approach is a method of study with a survey method, descriptive quantitative approach, data collection strategies are carried out randomly or randomly. A sample of 63 teachers was taken randomly from a population of 83 teachers. 1) descriptive quantitative analysis technique; and 2) multiple regression, the data analysis technique used. The results of the study suggested that 1) there was a major influence on teacher performance among the leadership of the principal; 2) there is an impact on teacher performance Significant impact on teacher performance between work motivation; and 3) there is a significant impact on teacher performance jointly between key leadership and work motivation